Effect of sodium bicarbonate and sodium bentonite on digestion and rumen fermentation characteristics of forage sorghum silage-based diets fed to growing steers - Jacques, K.A.; Axe, D.E.; Harris, T.R.; Harmon, D.L.; Bolsen, K.K.; Johnson, D.E. (Kansas Agricultural Experiment Station, 2012)
One percent sodium bicarbonate (NaHCo3) increased intake of a 50% silage - 50% grain diet, but had no effect on intake of a full-feed sorghum silage diet. The addition of concentrate (rolled milo) slightly lowered rumen pH and decreased acid detergent fiber (ADF) and starch digestion. NaHC03 had no effect on digestibility, but 2% bentonite lowered digestibility of NDF and ADF. Neither compound affected rumen fermentation characteristics.
Keywords: Dairy; Sodium bicarbonate; Sodium bentonite; Digestion; Fermentation; Steers; Sorghum silage